Editorial - Gonzales Muñiz, Nelly (2018)
Editorial ARQUITEK was born in 2006 as a proposal with academic content concerning the art of projecting and building buildings (Architecture) and planning and development of cities (Urbanism), in 2013 it becomes part of the Regional Online Information System for Journals Scientists from Latin America, the Caribbean, Spain and Portugal (LATINDEX) and assumes the significance of a scientific journal every six months. On this occasion, the thirteenth edition will be presented in digital format as of this year. The scientific journal ARQUITEK aims to disseminate scientific knowledge with quality criteria related to the content of research, technical characteristics, formal presentation, as well as the impact factor, covering research lines declared within the architectural field and including multidisciplinary material, helping in the increase of research productivity. The value of the journal not only resides in the authors of the scientific articles contributing to the knowledge from their extensive and accredited professional and research experience, in the national and international scope, but in the precious commitment of the external evaluators and the sustained work of the Editorial Committee, partners in the construction of this edition of ARQUITEK that presents selected topics entitled: Bioclimatic Housing Design Strategies; Comfort Term and Energy Saving in Housing; Trajectories of Urban Insertion in Sectors of Tacna; Reduction of Impacts due to Climate Change in Public Areas. This ARQUITEK journal edition contains six scientific articles listed above and integrates a section dedicated to results of community work of social impact carried out by architects without borders of "Ruta 4 Medellín - Colombia". This scientific journal edited by the Faculty of Architecture and Urbanism is aimed at architects, engineers, technologists, historians, art specialists and various professionals in order to promote scientific dissemination and to make it accessible. Dr. Nelly Gonzales Muñiz Dean of the Faculty of Architecture and Urbanism of the Private University of Tacna